2020
DOI: 10.1103/physrevlett.124.186601
|View full text |Cite
|
Sign up to set email alerts
|

Thouless Time Analysis of Anderson and Many-Body Localization Transitions

Abstract: Spectral statistics of disordered systems encode Thouless and Heisenberg time scales whose ratio determines whether the system is chaotic or localized. Identifying similarities between system size and disorder strength scaling of Thouless time for disordered quantum many-body systems with results for 3D and 5D Anderson models, we argue that the two-parameter scaling breaks down in the vicinity of the transition to the localized phase signalling subdiffusive dynamics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
115
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 215 publications
(122 citation statements)
references
References 108 publications
5
115
2
Order By: Relevance
“…Using an identical criterion one can reliably detect the well established Anderson localization transition in three (and higher) dimensions [12], thereby suggesting a link between the ergodicity breaking transition in disordered many-body systems and the Anderson localization transition.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…Using an identical criterion one can reliably detect the well established Anderson localization transition in three (and higher) dimensions [12], thereby suggesting a link between the ergodicity breaking transition in disordered many-body systems and the Anderson localization transition.…”
mentioning
confidence: 91%
“…A similar analysis to those in Figs. 2(c) and 2(f) has been recently performed for the three-dimensional (3d) and five-dimensional (5d) Anderson models [12]. It was shown that the critical disorder W c of the Anderson localization transition can be reliably detected using the same methodology as applied here, i.e., by requiring g = const when L increases (cf.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Such systems are directly amenable to experimental studies [18][19][20][21][22][23][24][25][26][27]. In this way we also stay away from a current vivid debate about the very existence of MBL in the thermodynamic limit [28][29][30][31][32]. We consider one-dimensional (1D) chains with chemical potentials quadratically dependent on position.…”
mentioning
confidence: 99%